Programming the HPA-axis by early life experience: Mechanisms of stress susceptibility and adaptation - Nikolaos P. Daskalakis (Frontiers Research Topics, 2015)
Experiences during early life program the central nervous- and endocrine-systems with consequences for susceptibility to physical and mental disorders. These programming effects depend on genetic and epigenetic factors, and their outcome leads to an adaptive or maladaptive phenotype to a given later environmental context. This Research Topic focused on the hypothalamus-pituitary-adrenal (HPA)-axis and stress-related phenotypes, and on how HPA-axis programming by the environment precisely occurs. We included original research, mini-review and review papers on a broad range of topics related to HPA-axis programming.